Bibliometric Analysis of Living Qur'an Research: A Dimensions Database Exploration (2005-2025) Using R for Statistical Computing and Bibliometrix Software - Ali, Asyiq Billah; Fi Ardillah, Maulida Fitri; Iwanebel, Fejrian Yazdajird; Taufik, Egi Tanadi (Suhuf: International Journal of Islamic Studies, 2025)
This research analyses the development of living Qur'an studies between 2005 and 2025 using the keywords “Living Qur’an”, “Living Al-Qur’an”, "Living Al-Quran", and “Living Al-Quran,” with two keywords containing no apostrophe. Data scraping and analysis rely on a bibliometric approach by analyzing utilizing tools such as R, VOSviewer, and Microsoft Excel to see the development of living Qur'an studies from the category of publications per year, average article citations, most publication sources, local impact of publication sources, most productive authors, most affiliated sources, and most cited documents globally in the database. The steps taken to categorize the data are as follows: determining keywords, searching for data, selecting articles, checking the validity of the data, and finally, analysis. The results showed that, since the emergence of the Living Qur'an from 2005 to 2025, the trend increased significantly from 2016 to 2022, peaking in 2022 with 99 articles. However, despite the increase in quantity, the academic impact of these articles is limited, as reflected in the journal's h-index. This finding also suggests that a university’s collective interest and productivity in the Living Qur'an discourse is not related to the presence of the discourse specialists in the given university.